Imperium w klimakterium: o współczesnej literaturze rosyjskiej z perspektywy hormonalnej = Empire during menopause : on contemporary Russian literature from a hormonal perspective - Thaidigsmann, Karoline (Teksty drugie, 2024)
The article analyzes the processes of remasculinization and demasculinization inpost-communist Russia, by focusing on the impact of these phenomena on VladimirPutin’s legitimization of power. The text presents literary representations of the crisis ofmasculinity in Russian culture using metaphors related to hormonal changes and midlifecrisis. It discusses the novels Sugar Kremlin by Vladimir Sorokin and Metro 2033 by DmitryGlukhovsky, which depict a society manipulated by autocratic power. Moreover, thearticle presents alternative visions of Russia’s future after an “andropause” in the contextof Maria Stepanova’s autobiographical-essayistic novel In Memory of Memory and LinorGoralik’s micro-stories, which provide a new perspective on Russian identity.